(untitled) (Oil and Gas Engineering, 2017)
The analysis of anthropogenic factors and proposes an improved generalized classification of anthropogenic impacts on the geological environment. Dedicated effects following classes: physical, physical-chemical, chemical, biological and combined. Class physical effects added by an electric wave and acts on the mountains. Keywords: human impact, geological environment, classification, analysis of anthropogenic factors.